ADSORPTION AT THE LIQUID SURFACE STUDIED BY MEANS OF SPECULAR REFLECTION OF NEUTRONS - Bradley, J; Lee, E; Lee, E; Thomas, R; Thomas, R; Willatt, A; Willatt, A; Penfold, J; Penfold, J; Ward, R; Ward, R; Gregory, D; et al. (1988)
The technique of specular reflection of neutrons has been used for the first time to study adsorption at the surface of water. Four systems were studied. The reflectivity profile of an insoluble monolayer of fully deuteriated butyl arachidate on water was measured as a function of surface pressure. The changes of reflectivity with surface concentration were found to be easily measurable. The thickness of the layer was found to be 35 ± 5 Å, about 15% larger than expected for the fully extended molecule. The surface of a solution of partially deuteriated decyltrimethylammonium bromide at about half the critical micelle concentration, where the monolayer is complete, gave a reflectivity profile corresponding to a layer thickness of 20 ± 8 Å and an area per molecule of 45 Å 2. The layer thickness is again slightly larger than expected for the fully extended molecule. The head group area agrees with independent estimates. Sodium dodecyl sulfate was studied as the protonated form in D 2O and the deuteriated form in H 2O/D 2O mixtures, demonstrating the potential of contrast variation in the specular reflection technique. The thickness of the layer was found to be 20 Å in both cases, and estimates of the distribution of water in the layer were made at different concentrations. The deuteriated surfactant contained about 10% dodecanol as impurity. At low concentrations the layer was found to be 100% dodecanol, but, as the concentration increased above about one-tenth of the critical micelle concentration (8.1 × 10 -3 M), dodecanol was increasingly replaced in the layer by sodium dodecyl sulfate. © 1988 American Chemical Society.